Pendampingan Layanan Konseling Individu sebagai Upaya Pencegahan Masalah Sosial-Emosional Siswa di SMPI Integral Lukman Alhakim 02 Batam - Afrizawati; Yuliana; Al Hidayah; Nur Selihatun; Hadijah Hulopi (SIGMA : Jurnal Sinergi Mengabdi, 2025)
Social-emotional problems among junior high school students—such as anxiety, low self-confidence, difficulty in building peer relationships, and behavioral issues—are significant challenges that can hinder both academic and personal development. One preventive approach to address these issues is through structured and professional individual counseling services. This community service program aimed to enhance the capacity of guidance and counseling (BK) teachers in implementing individual counseling as a means of preventing students’ social-emotional problems. The program was carried out at SMPI Integral Lukman Alhakim 02 Batam through three main stages: preparation, implementation, and evaluation. The methods involved workshops, simulation practices, supervision, and evaluation using pre-tests and post-tests. The results showed a significant improvement in the understanding and skills of BK teachers in conducting individual counseling. Participant reflections also indicated that the assistance was highly beneficial in helping them implement counseling services more systematically and effectively. This activity highlights the importance of strengthening the capacity of BK teachers as the front-liners in identifying and managing students’ social-emotional challenges through preventive interventions.